Implementação do Windows 2008 Server - Juttel, Djones Carlos (2012)
The purpose of this monograph is to present information security on servers that provide information focused on the internal network of the Accounting Office St. Benedict. First, we present the concepts of several topics covered at work, as computer networks, operating system Windows Server 2008, GPO, OU, security policies, restrictions. The emphasis of this study was to apply a set of rules and restrictions for administering an effective way all drives in the domain of internal network, resulting in greater reliability, security and monitoring.